Potential impact of climate change on crop insect pests and diseases in Bangladesh: Future scenarios and strategies for climate services - Salam, Moin; Krupnik, Timothy J.; Montes, Carlos; Nessa, Bodrun; Khatun, Mst. Tuhina; Ali, Md. Panna; Shahrin, Sumona; Ishtiaque, Sheikh; Mannan, Md. Abdul; Hassan, S.M. Quamrul; Aziz, Mazhar; Uddin, M. Shahab (Krishi Gobeshona Foundation, 2019)
Insect pest and disease outbreaks are driven by the environmental factors, presence of susceptible crop plants, and insect pest or pathogen population. Future climate variability and climate change (CC) are expected to modify the distribution and severity of pest damage and disease epidemics. In this paper, we present (i) an overview of the major and emerging insect pests and diseases of key field crops and associated yield losses, (ii) an analysis of historical and future climate scenarios and potential infestation of the agents, (iii) a framework to support integrated pest and disease management, and (iv) recommendations towards policies and actions. We have utilized modeling approaches to provide a preliminary estimate of the potential changes in three insect pests and 14 disease species with three future time-slices.